Description of new andean species of the genus Phymaturus (Iguania: Liolaemidae) from Northwestern Argentina - Lobo, Fernando; Laspiur, Alejandro; Acosta, Juan Carlos (Zootaxa, 2013)
As a result of several field trips and studies of collections of Phymaturus samples from Andean areas of central western Argentina (San Juan province), we discovered two populations that exhibit a particular character combination not seen in other species formally recognized in the literature. Based on a detailed analysis of an extended list of morphological characters (93), including scalation, color pattern, gular and nuchal folds, precloacal pores, and morphometric data, we conclude that these populations represent independent lineages that deserve to be considered as new species. According to the most recent revision of the genus and considering the descriptions made in another recent contribution, the taxo-nomic composition of the genus was increased to 38 species. In this study we provide the formal description of two addi-tional new taxa, including their diagnosis and detailed comparisons with other members of their species group. The two new species belong to the palluma group, and can be assigned to the Puna subclade because they present the typical dorsal “spray” pattern. Other characters described in this study suggest their close phylogenetic relationship with other species of this subclade inhabiting the southern Puna region of Argentina, such as Phymaturus punae. Within the Puna subclade, Phymaturus aguanegra sp. nov. differs from all other members (P. antofagastensis, P. denotatus, P. laurenti, P. punae, P. extrilidus, P. mallimaccii and P. paihuanense) exhibiting the following combination of diagnostic characters: a complete melanism over the dorsum of neck, the presence of enlarged scales at the base of tail in males, having strongly keeled tarsal scales, lacking enlarged scales on the anterior margin of the antehumeral fold and centre of chest, females without flank coloration, a vertebral dark gray stripe usually present on the dorsum, females exhibiting a tricolor dorsal pattern, with two types of brown and scattered ferriferous oxide spots, and the absence of a scapular spot. Phymaturus williamsi sp. nov. differs from all other members of the Puna clade because: exhibits an “aggregate” dorsal pattern, unlike the ho-mogeneous spray of most Puna species, lacks enlarged scales on the anterior margin of the antehumeral fold and in the centre of chest, flank coloration in females is absent, females of Phymaturus williamsi sp. nov. lack white transversal stripes on the dorsal pattern, preocular scale in contact with canthal scale in Phymaturus williamsi sp. nov., rostral scale can be divided in Phymaturus williamsi sp. nov. and shows the largest number of scales counted around midbody within the Puna subclade (x= 213.4; 186-235).